Changes of Catholic Church in Lithuania in Time of Transformations - Pruskus, Valdas (Problemos, 2003)
After the restoration of independence of Lithuania, changing of Catholic Church as an institution was predetermined by two most important factors. One of them was the heritage of the anti-church policy promoted in the Soviet times. The other one was the fact that on the transition from the earlier social links with a civic society the Church comes into collision with new Challenges and looks for an ade- quate responsc in the presence of rapidly developing transformations. The fonnal renovation of the Church within the first decade of independence by retuming to its earlier prohibited spheres and means of activities brought to light the new sources of tension (external and internal) 60 of growing of the Church as an institution. The exter- nal sources are bound with the myths which appeared in the times of Sąjūdis and have failed already - the overrating of the force of the Church and its possibi- lities to influence the society as well as the insufficient estimation of expressions of the enmity to the Church. The internal sources include: a lack of an adequate communication with the modern pluralistic society using influential means; a conflict between the general wel- fare and the interests of an individual (a group) in a settlement of affairs of the Church; clashes of conservative priests and supporters of making the Church more modem. The listed sources of tension bring to light the real outlinc of the position and influence of the Church in the society as well as its political influ- cnce. The attitude of the Catholic Church with respect to the state within the last decadc may be charactcrizcd with three csscntial factors. First, the Catholic Church declarcd that in principle it agrces with a democratic political regime, howevcr, it is far from being truth that such almost declarativc approval of a demoeraey means identical perception of the principles of democracy, in particular freedom and tolerance, in various strata of believers. Second, the Church was looking for ways and me- ans to disclosc its relations with political parties. The Church was trying to maintain a moderatc position with respect to political parties, because they have not sufficiently clearly defined their ideologíeal identity and have not expressed clearly their position with respect to the Church. Their attitude is often caused by one-day conjuncture conditions. Third, the Catholic Church in Lithuania is not disposed to affiliate itself both with the national idea and nationalism. This standpoint has long-year traditions, formned before the war, and, in course of strenghthening of the links of the Catholic Church with Protestant, Orthodox and even Old Believer communities, it made the atmosphere of suspiciousness, alie- nation and distrust more healthy and in this way helped to reduce the tensions between Lithuanians and national minorities of Lithuania. Įteikta 2002 04 15 ln spitc of an indubitable positive influence of the Catholic Church upon an improvement of the social organization of the society and a formation of a civic society in Lithuania, it becomes more and more clear that the state (although the espeeially honorable position of the Church, forrned in course of history de jure for its merits in development of sclf-consciousness of the nation and protection of its identity) de facto gradually is ceasing to consider the Church as organization with special status. If civic society is defined as system of various groups, socicties, unions, the Church becomes one of many groups of interest. Being a group of interest means the following to the Church. First - a loosing of the certain a priori predetermined position which does not look well from the standpoint of demoeratic plura- lism proper to civic society. Second - the relations of the Church as an institution with other public institutions are defined more clearly and a neeessity to strive for a realization of its interests (ideas, thoughts, opinions) in a competition with other (religious groups) is better realized. It was a peculiar challenge both to the Church and believers. The Church was induced to find ways of action oorresponding to the needs of the society. The believers were induced not only attcst publicly their Christian faith, but also effectively protect it.